Sentido das mudanças: economia criativa e implicações sociais em Porto Alegre - Sandro Ruduit Garcia (Ciências Sociais Unisinos, 2017)
Creative economy has been the subject of a recent and successful academic production of different specialties in different countries, recording social, political and cultural changes involved in it. This article addresses the sense of the changes, recognized in international experience, in our context, centrally inquiring about: what kind of social implications takes place due to the growth of activities in companies in the sectors of creative economy? It starts from the recognition that economic action finds itself immersed in a set of mechanisms of social mediation. Data were obtained on a purposeful sample of fourteen small enterprises belonging to this economy in the city of Porto Alegre, complementing with documentary sources. The study suggests that this type of business tends to be guided by the pursuit of novelty, complementarity of knowledge, professional autonomy and responsibility with the environment, within the limits of the social and institutional conditions in which they take part.